Temperature of Precipitation Hardening and its Effect on Mechanical and Physical Properties of Zr Containing AlSi5Cu2Mg Alloy - D. Bolibruchová; M. Sýkorová; M. Chalupová (Archives of Metallurgy and Materials)
The paper examines the effect of precipitation hardening temperature on selected properties of AlSi5Cu2Mg alloy alloyed by 0.20 wt.% of Zr. The newly developed AlSi5Cu2Mg alloy intended for cylinder head castings is specific due to its limited Ti content, which prevents the use of standard Al-Ti-B type grain refiners. Zr added in the form of AlZr20 master alloy acts as a grain refiner. The grain refinement effect of Zr positively affects the mechanical properties. However, the physical properties defining the lifetime of cylinder head castings are not affected by the presence of Zr-rich phases. For this reason, the research focuses on the proposal of the optimal T6 heat treatment procedure in order to positively influence the physical and mechanical properties of the AlSi5Cu2Mg alloy. For the research, four T6 thermal regimes with graduated aging temperatures by 20°C from 180 to 240°C ± 5°C were selected. The results showed that increasing aging temperature positively affects physical properties, especially thermal conductivity, and mechanical properties of Rm, Rp0.2, and HBW. On the other hand, with increasing aging temperature up to 220°C ± 5°C, a negative decrease in ductility was achieved. Optimum ductility of, especially, AlSi5Cu2Mg alloy with 0.20 wt.% Zr was achieved by the T6-240 thermal regime. Optimal combination of thermal conductivity and mechanical properties of the AlSi5Cu2Mg alloy with 0.20 wt.% Zr was achieved by the T6-240 heat treatment due to the requirements placed on cylinder head castings.